Yield and Strength Properties of Pulp of some Clones of Eucalyptus tereticornis Sm. - Rao, R. V.; Kothiyal, V.; Sreevani, P.; Shashikala, S.; Naithani, S.; Singh, S. V. (Indian Forester, 1999)
Five trees of four and half years old growth representing 5 clones of Eucalyptus tereticornis Sm. Obtained from ITC Bhadrachalam Paper Boards, Andhra Pradesh, India were evaluated for pulp yield and strength properties. Variation in pulp yield, kappa number, holocellulose and lignin content, strength and anatomical properties was observed in five clones. Clone 3 yielded more pulp. The pulps of all the clones tested have adequate strength properties. Basic information on anatomical properties were also provided in the paper.